Clinical and research follow-up for knee cartilage injuries-an international consensus statement - Isabel P. Prado; Eoghan T. Hurley; Richard M. Danilkowicz; Asheesh Bedi; Alexander Golant; John A. Grant; Andrew J. Hughes; Mike McNicholas; Matthew Salzler; Ian Savage-Elliott; Aaron J. Krych (Elsevier, 2024)
Introduction: Articular cartilage injuries of the knee are a complex and challenging clinical pathology. Objectives: The purpose of this study was to establish consensus statements via a Delphi process on clinical and research follow-up for knee cartilage injuries. Methods: A consensus process on knee cartilage injuries utilizing a modified Delphi technique was conducted. Seventy-seven surgeons across 17 countries were invited to participate in these consensus statements. Nine questions were generated on clinical and research follow-up, with 3 rounds of questionnaires and final voting occurring. Consensus was defined as achieving 80% to 89% agreement, whereas strong consensus was defined as 90% to 99% agreement, and unanimous consensus was defined as 100% agreement with a proposed statement. Results: Of the 9 total questions and consensus statements on clinical and research follow-up developed from 3 rounds of voting, 1 achieved unanimous consensus, 5 achieved strong consensus, 1 achieved consensus, and 2 did not achieve consensus. Conclusions: The statement that achieved unanimous consensus was on physical examination findings. The statements that achieved strong consensus were related to defining and monitoring treatment success, patient-reported outcomes, research follow-up, and second-look arthroscopy in the setting of recurrence. The statements that did not achieve consensus were related to routine imaging and length of clinical follow-up after operative intervention.